Extreme endurance athletes and oxidative stress: effect of multivitamin and trace element supplementation during the "Marathon des Sables" - Machefer, G.; Groussard, C.; Zouhal, H.; Vincent, E.; Radak, Z.; Faure, H.; Malarde, L.; Gratas-Delamarche, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The competition entitled the "Marathon des Sables" (MDS) is a self-sufficient diet running competition that consists in 6 exhaustive races during 7 days. It takes place under intense thermal stress in Moroccan desert. These three conditions, limited diet, repetition of exhaustive exercises and heat exposure are known to promote oxidative stress. The aims of the study were to 1) measured the dietary intake of the athletes participating to the MDS; and to 2) investigate the effects of a moderate multivitamin and trace element supplementation prior to and during the MDS on the blood antioxidant status and oxidative stress markers. Methods: Twenty-three trained athletes (174.1±1.3cm; 68.1±1.6kg; VO2max:59.6±1.2ml.min-1.kg-1) who voluntary participated in the MDS were included in the first part of the study. A basal blood sample was obtained 3 weeks prior to the start of the MDS. These athletes kept a food record during the week prior to this basal blood sample. Seventeen endurance trained athletes participated in the second part of the study. At the beginning of the study, 3 weeks before the MDS, a first blood sample (D-21) was obtained and the athletes were then randomly divided into a Supplemented group (S) (10 men; 174.9±2.7cm; 70.4±3.2kg; VO2max:58.8±1.1ml.min-1.kg-1) and a Placebo group (P) (6 men and 1 woman; 173.1±1.6cm; 64.9±2.9kg; VO2max:58.9±0.5ml.min-1.kg-1). Supplemented subjects took three tablets per day of Isoxan-Endurance® (NHS, Paris, Rungis, France) which contained mainly vitamin C (50.0 mg), vitamin E (8.0 mg) and â-carotene (1.6 mg) during three weeks before the competition and during the week of competition. Placebo subjects consumed three tablets which had similar form and taste but without antioxidant vitamins. Three other blood samples were obtained: 2 days prior to the start of the MDS (D-2), after 3 races (D3) and at the end of the MDS on day 7 (D7). In both parts of the study, oxidative stress markers (plasma thiobarbituric reactive substances (TBARS) and protein carbonyl derivative (RCD)), markers of muscle damage (plasma creatine kinase and lactico deshydrogenase activities), antioxidant status (erythrocyte glutathione, superoxide dismutase and glutathione peroxidase activities; plasma uric acid) and antioxidant vitamins (plasma vitamin C, Alpha-tocopherol, Beta-carotene and retinol) were measured. Statistical analysis required a student t-test and ANOVA with repeated measures. Correlation was attested by a Pearson test. Results: First part of the study: Athlete`s energy intake was 2287.4±138.3 Kcal.d-1 (34.8±2.5Kcal.d-1.kg-1) three weeks before the MDS. Retinol equivalent (retinol + Beta-carotene) intakes (1.39±0.2 vs 0.9±0.02mg.d-1) was significantly higher than the DRI for sports population whereas Alpha-tocopherol intake (7.68±1.4 vs 14.95±1.21mg.d-1) was significantly lower. Vitamin C intake was no significantly different from the DRI (175.11±28.2 vs 135.10±9.99mg.d-1). Plasma Beta-carotene concentration was correlated with Beta-carotene intake (r=0,52; p<0,05). Second part of the study: 3 weeks of multivitamin and trace element supplementation increased significantly plasma Alpha-tocopherol, Beta-carotene and retinol levels in the S group at rest. During the race, TBARS level increased significantly at D3 only in the P group (fig.1) and returned to the basal values on D7. At the opposite, RCD level was not modified during the study in both groups. Muscle damage markers increased during the MDS in both groups. Vitamin C level was significantly increased and Alpha-tocopherol and retinol levels were decreased on D7 only in the S group but no significant changes were observed in P group. No significant differences between the two groups were obtained in the other parameters recorded in this study. Discussion/conclusion: Athlete`s energy intake was low compared with sport population. The important vitamin C and retinol equivalent intakes and the low Alpha-tocopherol intake were due to high intakes in fruits and vegetables but low intakes in oil and fat nutrient. These results had already been observed in physical education students (Groussard et al. 2004). This study showed that moderate multivitamins and antioxidant supplementation increased plasma antioxidant vitamins and prevented the transient increase in TBARS production caused by the extreme exercise. Moreover, the utilization and/or mobilization of antioxidant vitamins were greater with the supplementation. However, this supplementation did not limit muscle damage. As TBARS returned to the basal values on D7 in the P group, an adaptive response seemed to occur in this group after only 6 repetitions of long races.